Revisión sistemática de literatura sobre factores clave en la identificación de oportunidades de negocio - Gamero, Harold (2020)
The identification of business opportunities is a determining task within the dynamics of entrepreneurship. Therefore, different researches have sought relationships between individual factors and the successful results of this first entrepreneurial step. Although numerous factors have been analyzed, there is still a considerable extension of definitions that vary between them. In response to this need, this article develops a systematic review of the literature, consolidating those factors that have been included in this research field during the last ten years. This review was carried out following the Jennifer Platt three-stage methodology, which has been widely used in similar articles. Starting from a total of 3119 articles, a systematic depuration was carried out resulting in an analysis of 30 articles. The results of this study indicate that there are about 22 proposed factors, with five being the most important among them, that facilitate the identification of business opportunities: prior knowledge, entrepreneurial alertness, self-efficacy, creativity, and contact networks. Other factors found in the analysis are: entrepreneurship experience, work experience, education, cognitive abilities, entrepreneurship intentions and the active search for opportunities in the market. This work contributes to the literature by summarizing the factors included in multiple investigations and offering future lines of research for academics interested in the area.